Analisis Pengalaman Pengguna Website lakonmandira.kaboki.go.id Menggunakan Metode User Experience Questionnaire - Mayang Sari, Anisa; Fathiyah Nopriani; Indah Hidayanti (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2026)
The lakonmandira.kaboki.go.id website is one of the government services that aims to make it easier for the people of Ogan Komering Ilir to make online submissions. In use, there are still often complaints from users, including, no user franly, no search feature, no chat feature to facilitate two-way communication, no data editing feature on returned submissions, websites tend to be monotonous and unattractive, and there has never been a system upgrade since it was last released. This problem is related to six assessment scales in the UEQ method, namely, Attractivness, Perspicuity, Efficiency, Dependenbility, stimulation, and novelty. To overcome these problems, a user experience analysis will be carried out using the User Experience Questionnaire (UEQ) method. The respondent data used was 179 out of 335 populations, the UEQ calculation process was carried out using the UEQ analysis data tool to determine the level of user experience at each scale. The results of this finding show the paramenter results of attractiveness (1.17), clarity (0.9), efficiency (0.64), reliability (1.11), stimulation (1.39), novelty (1.4). The results show that the scale of attractiveness, clarity, efficiency, reliability is in the "below average" category which is a priority for improvement and the scale of stimulation and novelty is in the "good" category. Kata Kunci: Website, User Experience Questionnaire, lakonmandira.go.id